Analisis Faktor-Faktor yang Mempengaruhi Minat UMKM Mengajukan Kredit ULaMM pada PT Permodalan Nasional Madani (Persero) KCP Kendal - Putri, Abillah; Kusuma, Septian Yudha; Kodir, Moch Abdul (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2022)
The purpose of this study was to determine the effect of interest rates, collateral or credit guarantees and credit procedures on the interest of MSMEs in applying for ULaMM credit at PT Permodalan Nasional Madani (Persero) KCP Kendal. The population in this study were all customers who took ULaMM credit at PT Permodalan Nasional Madani (Persero). The sampling technique used is purposive sampling as many as 90 respondents. The data taken in this study are primary data obtained through the distribution of questionnaires to the intended respondents. The analytical tools used in this study are multiple linear regression analysis, F test, determinant coefficient test (R²) and T test. Based on the test results in this study, the determinant coefficient test (R²) shows a value of 50.1%. The results of the hypothesis test conducted indicate that the interest rate and collateral or credit guarantees have a positive and significant effect on the interest of MSMEs in applying for ULaMM credit, while the credit procedure has an insignificant positive effect on the interest of MSMEs in applying for ULaMM loans.